Analisis Program Smart Class Award Sebagai Upaya Meningkatkan Nilai-Nilai Kompetisi Siswa di MA Muhammadiyah 09 Lamongan - Faridah .; Khotimatus Sholikhah; Siti Latihfatus Sun'iyah (AJER: Advanced Journal of Education and Religion, 2025)
The Smart Class Award program has become a primary focus in efforts to improve the quality of education in various institutions, particularly at Madrasah Aliyah Muhammadiyah 09 Lamongan. This phenomenon is intriguing to study considering the challenges faced by Islamic educational institutions in creating a competitive learning environment with character aligned with the Pancasila student profile. This program is designed to address issues of discipline and classroom facility maintenance as well as to enhance student character, including faith, independence, creativity, global awareness, and critical thinking skills. This study aims to analyze the implementation of the Smart Class Award Program at MA Muhammadiyah 09 Lamongan, identify the challenges and obstacles encountered, and the factors influencing its success. Using a qualitative research method, data were obtained through in-depth interviews with various informants, including teachers, students, and the school principal. The data were then analyzed to understand how the program is implemented and its impact on the competitive values among students. The results of the study show that the Smart Class Award Program is effective in enhancing student competitiveness, as evidenced by increased collaboration, care, and willingness to share among students. The program also successfully improves student discipline in various aspects, including class attendance, uniform discipline, and school administration. However, the study also identifies several challenges, such as limited facilities and uneven economic conditions among students. Supporting factors for the program’s success include the boarding conditions of the students, which facilitate communication and class management, and the availability of sufficient time to manage the class, despite sacrificing some rest time. In conclusion, the Smart Class Award Program has great potential to continue improving the quality of education at MA Muhammadiyah 09 Lamongan, provided that the existing challenges are adequately addressed.